Pengembangan E-Modul Praktikum Berbasis Kimia Komputasi Tentang Bentuk Dasar Molekul - Dewi, Ella Gia; Anwar, Yunita Arian Sani; Hakim, Aliefman (Chemistry Education Practice, 2024)
This study aims to develop an e-module based on computational chemistry based on molecular shape. The type of research used is research and development (R&D). This development model uses a 4D model. The sampling technique used is simple random sampling. The population of this study was students of class X MIA SMAN 9 Mataram, amounting to 144 people and 23 people were taken as samples. Data collection techniques using interviews and questionnaires. The results showed that (1) the developed e-module can show the shape of the compound in 2D or 3D, (2) the results of the analysis of the e-module validation sheet for computational chemistrybased chemistry practicum on the basic shape of the molecule assessed by two validating (experts) was obtained. the value of V, which is 0.6, Is in the valid category, (3) the results of the analysis of student responses using response questionnaires       for all aspects obtained on average students respond well to the computational chemistry-based chemistry practicum e-module about the basic shape of the molecule developed on average. The average practicality of the student response questionnaire are 80% with a very practical category. Based on these data, it can be concluded that the computational chemistry-based chemistry practicum e-module on the basic molecular shape material developed is feasible and very practical to use in the learning process.